Counter hegemonic representation of Islamic media in Indonesia on death penalty issue - Yuri Alfrin Aladdin; Soraya Fadhal; Joshua Fernando (Bricolage : Jurnal Magister Ilmu Komunikasi, 2022)
During the first two years of Jokowi-Jusuf Kalla Government (2014-2015) in Indonesia, precisely 18 death row inmates who were guilty of drugs had been executed. The government believed that death penalty is the effective solution to overcome the high rate of narcotics crime. It becomes an interesting case due to the pressure of hegemony of the European Union over the government of Indonesia. One of the major national media in Indonesia, namely Republika.co.id, supports the implementation of death penalty. This studied aims to reveal the counter-hegemonic representation of Republika.co.id in opposing the hegemony of the EU related to the issue of Human Rights, particularly death penalty. This study applied Critical Discourse Analysis by Norman Fairclough and critical theory of Hegemony by Antonio Gramsci. The result shown that Republika represents counter-hegemonic in its reporting since it rejects the EU’s attitude considered to impose its standard principles of human rights on Indonesia.